New records of fleas and ticks in armadillos (Xenarthra: Chlamyphoridae) from the Espinal and Monte ecoregions of La Pampa province, Argentina - Ezquiaga, María Cecilia; Soibelzon, Esteban (Zootaxa, 2021)
La Pampa province is divided into two clearly distinguishable fractions: a small northeastern humid sector corresponding to the Pampas ecoregion and a drier western sector, represented by the Monte de Llanuras y Mesetas (termed Monte region in this paper) and Espinal ecoregions (sensu Brown et al. 2006). These three ecoregions are visibly distinguishable from an edaphological and phytogeographic point of view, while the mammalian fauna composition is homogeneous. The study area was located in the central part of the province, comprising the Monte and Espinal ecoregions (Fig. 1). In that area three species of armadillos are recorded (Soibelzon et al. 2015). Two of these (Zaedyus pichiy Desmarest, 1804 and Chaetophractus villosus Desmarest, 1804) (Xenarthra: Chlamyphoridae) are the most common and widely distributed armadillos both in the province and in the country, while the third species, Chlamyphorus truncatus Harlan, 1825, has a more restricted distribution and is one of the most cryptic and least known armadillos in the country. For this reason, in our fieldwork ectoparasites were obtained only from the first two species mentioned.